A framework for selection of logistics outsourcing partner in uncertain environment using TOPSIS. (1st January 2012) - Gupta, Rajesh; Sachdeva, Anish; Bhardwaj, Arvind
With globalisation and liberalisation, the markets are turning competitive. The key area for industry now is to make the product available to the end customer in time, without damage and loss due to over or under stocking. Hence, logistics is seen as an important area where industries can cut costs and improve their customer service quality. The latest trend is to outsource logistics activities to allow the outsourcing company to concentrate on the core competence, improve the service and reduce the capital cost. In this paper, a framework is proposed to select the most suitable outside Logistics Company (3PL) using fuzzy Delphi method to shortlist the most important criteria and fuzzy technique for order performance by similarity to idea solution (TOPSIS) to choose the best 3PL by finding the closeness to the positive ideal solution. The weights to the opinion of decision-makers (DMs) are assigned according to their qualification, experience and designation. The integrated approach of fuzzy Delphi and fuzzy TOPSIS enhances the accuracy of the result and proves to be helpful for the DMs. A case study is conducted in an automobile company in North India to select the best suitable 3PL service providers to demonstrate the proposed methodology.